THE ANALYSIS OF DIABETES SELF-MANAGEMENT IMPLEMENTATION ON TYPE 2 DIABETES MELLITUS PATIENTS: A PROTOCOL FOR SYSTEMATIC REVIEW AND META-ANALYSIS - Salsabila, Zhafirah; Sjaaf, Amal C (Jurnal Ekonomi Kesehatan Indonesia, 2022)
Diabetes is the fourth leading cause of death in the world. Ninety percent of the world's DM cases are dominated by type 2. International Diabetes Federation predicted the incidence and mortality rate of diabetes are increasing by 2045. Diabetes causes macrovascular complications that contribute to cardiovascular death, and microvascular which a risk factor for blindness, lower-extremity amputation, kidney failure, and death. One of the efforts to control complications from diabetes is done through diabetes self-management consists of education, medical nutrition therapy, pharmacological therapy, and physical exercise. The main purpose of implementing DSM is that patients can prevent or slow the onset of complications from diabetes itself. This study aims to summarize and systematically synthesize the clinical and non-clinical effectiveness and resume the cost-analysis of DSM implementation. Several electronic databases will be used: Medline via PubMed, and Embase. The complete evidence will be summarized and critically appraised using Cochrane guidelines and JBI Critical Appraisal Checklist for RCT and cohort studies. In terms of analysis, we will qualitative-quantitatively appraise and present the studies that meet our inclusion criteria. We are expected to summarize the quality and capture the valuable insights related to the study of effectiveness in implementing diabetes self-management of T2DM.